2021
DOI: 10.1007/s10570-021-04081-5
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Dispersion and Setting of Cellulose Nanofibril - Carboxymethyl Cellulose Pastes

Abstract: This work investigated the redispersion and setting behavior of highly loaded (~18 wt.% solids in water) pastes of cellulose nano brils (CNFs) with carboxymethyl cellulose (CMC). A single-screw extruder was used to continuously process CNF+CMC pastes into cord. The adsorption of CMC onto the CNF brils was assessed through zeta potential and titration which revealed a surface charge change of ~61 % from -36.8 mV and 0.094 mmol/g COOH for pure CNF to -58.1 mV and 0.166 mmol/g COOH for CNF+CMC with a CMC degree o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 66 publications
1
5
0
Order By: Relevance
“…Sharma & Deng (2016) also reported that this crosslinking not only improved the wet strength but also improved the dry strength of cellulose nanofibril films through a dual mechanism of crosslinking and hornification that occurred during the curing process at a high temperature . A recent report also described a similar crosslinking mechanism between the CMC and PAE chains, which is more indicative of our system under study …”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…Sharma & Deng (2016) also reported that this crosslinking not only improved the wet strength but also improved the dry strength of cellulose nanofibril films through a dual mechanism of crosslinking and hornification that occurred during the curing process at a high temperature . A recent report also described a similar crosslinking mechanism between the CMC and PAE chains, which is more indicative of our system under study …”
Section: Resultssupporting
confidence: 56%
“…39 A recent report also described a similar crosslinking mechanism between the CMC and PAE chains, which is more indicative of our system under study. 40 To confirm if a similar ester linkage occurred in our films, we performed FTIR analysis as illustrated in Figure 2b,c. However, due to the presence of lignin and other additive materials in OCC-LCNFs, the FTIR spectra of pristine LCNF films showed a wide range of functional groups, including the majority of the functional groups expected to be present after crosslinking.…”
Section: ■ Results and Discussionmentioning
confidence: 86%
“…Indeed, several types of interactions could be involved in these formulations. First, van der Waals interactions and hydrogen bonding between mCMC and CNC or mCNC could occur, even in the presence of negative charges brought by carboxylate groups on the mCMC backbone. ,, The lower surface sulfate content of mCNCs could probably facilitate the surface absorption of mCMC onto the nanorods. Due to the presence of methacrylate groups on both mCMC and mCNC, hydrophobic interactions between these two compounds could also occur, increasing the possibility of mCMC adsorption on mCNCs.…”
Section: Resultsmentioning
confidence: 99%
“…The ζ-potential increased from +2.2 mV for the CNF to +48.8 mV for the CCNF, indicating that the mutual repulsion of the electric double layer between CCNF molecules was far greater than van der Waals’ attraction according to the Derjaguin, Landau, Verwey, and Overbeek (DLVO) theory. Therefore, the formed energy barrier prevented the molecules from being close and the Debye length was enhanced as well . As colloid molecules became scattered, the stability of the dispersion was promoted remarkably.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the formed energy barrier prevented the molecules from being close and the Debye length was enhanced as well. 36 As colloid molecules became scattered, the stability of the dispersion was promoted remarkably. Furthermore, CCNF could reach 300 nm−1 μm in length and 1−5 nm in diameter, detected by AMF as shown in Figure S2, showing an incomparable advantage in the application of stabilizing foam.…”
Section: Structural Characterization Of the Ccnfmentioning
confidence: 99%